Effects of platescapes on plate waste percentage among patients in a public hospital in Selangor, Malaysia - Shalihin, Siti Amirah Shaheera (2022)
The prevalence of plate waste in the hospital setting is concerning as it reflects the patients’ nutrition inadequacy. There are many studies conducted to improve hospital plate waste but there is limited study determine the effect of platescapes on plate waste percentage in the hospital setting. Platescapes or the visual physical characteristics of the dinnerware are some factors patients observe during the meal that could mold food behavior and food intake without involving the taste, texture, or quality of the food itself. Therefore, this quasi-experimental study aimed to determine the effect of platescapes (1) Experimental Compartment Blue Tray (CBlT) and Control Compartment Beige Tray (CBgT) and (2) Experimental Blue Plate (BP) and Control White Plate (WP) for Plate Colours Experiment on plate waste percentage during one time lunch hour among patients in a public hospital in Selangor who received a normal diet. This study also determined the interaction of the tray/plate colours and the main effect of socio-demographic characteristics (sex, age, ethnicity, household income, employment status), medical background (ward specialty, length of stay), nutritional status (BMI, nutritional risk), appetite level and hospital food service satisfaction (food quality, meal service and staff issue, customization, physical and social and overall satisfaction) with plate waste percentage. The findings of this study showed that the plate waste percentage in the Tray Experiment was 30.1%. For the Plate Experiment, the total plate waste percentage was 32.5%. There was a statistically significant difference in total plate waste percentage between the plate colours (with lower plate waste percentage was reported in BP group. The highest reason for plate waste reported by patients in the Tray Experiment was due to poor appetite. Interestingly, the Plate Experiment showed the most frequent reason was different food preference/meal taste. The TWO-WAY ANOVA was conducted to determine the interaction between the tray or plate colour with the baseline variables. The result shows that there was only a significant interaction effect found between the plate colours and education level. The analysis of the main effect for the Tray Experiment shows, ethnicity and overall satisfaction were significantly related with plate waste percentage. There were significant effect of food quality and overall satisfaction, with plate waste percentage with the trend of higher food quality or overall satisfaction will result in a lower plate waste percentage. For the Plate Experiment, the findings show, male was associated with a lower mean of plate waste percentage than female. The oncology ward specialty was associated with a higher mean of plate waste percentage 37.9% than orthopedics. There is a significant main effect between BMI category with plate waste percentage. After controlling for the covariates, the plate waste percentage between the Experimental Blue Plate and Control White Plate remain significant. The result of this study can help health professionals to consider improvising platescapes as part of the strategies to manage inadequacy of food intake issues and plate waste problems in the hospital as well as enliven the dining experience among the patients.